Quality of life of elderly population in Sri Lanka - Muhammed, Munfika (University of Colombo, 2015)
The ageing of Sri Lanka's population is one of the most serious socio-economic challenges in the coming decades. Although the Budget of 2015 recognized this to some extent, no significant steps have been taken to cope with the problems of an ageing population. Weak public finances, distorted prioritization of public expenditure and wasteful expenditure leave no fiscal space to address the needs of the elderly. The inability to reform the retirement age and retirement benefits compound the econornic and social problems of an ageing society. Nevertheless it is important to highlight the emerging problems of the country's ageing population. Sri Lanka currently experiences a significant increase of aging population together with poverty and breakdown of various social and traditional bonds.
Keywords: Ageing population, socio-economic challenges, elderly population